HUBUNGAN ANTARA DERAJAT KEPARAHAN SIROSIS HATI DENGAN DERAJAT DISFUNGSI EREKSI PADA PASIEN SIROSIS HATI - , Rachmad Aji Saksana, Prof. Dr. Siti Nurjanah, SpPD., K-GEH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Liver cirrhosis causes impairment in most of the liver function including the hormonal balance and metabolism of steroids. In male, liver cirrhosis causes hypogonadism and feminization. Sexual dysfunction in cirrhotic patients is still underestimated and underdiagnosed because not as a life-threatening complications, hence patients do not seek help, however, it affects the quality of life patients and his partner. The most common sexual dysfunction in male cirrhotic patients is impotence or erectile dysfunction. Despite the prevalence of erectile dysfunction is high in patients with liver cirrhosis, only few studies revealing the relationship between severity of liver cirrhosis and severity of erectile dysfunction. The purpose of this study is to determine the correlation between severity of liver cirrhosis (child pugh score) and severity of erectile dysfunction (IIEF-5 score) in cirrhosis patients. We conducted a cross sectional study. Subjects were patients of liver cirrhosis, male, age 18 to 65 years old, married, have partner, and agreed to participate this study. We used Pearson corelation to assess corelation between severity of liver cirrhosis (child pugh score) and severity of erectile dysfunction (score of IIEF-5), if the data were distributed normally and Spearman corelation as an alternative.